The Ability of Indonesian EFL University Students in Writing an Explanation Text - Yanpitherszon Liunokas (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2020)
This research aims at finding out the students’ ability in writing an explanation at first semester students of English Study Program of Nusa Cendana University, Kupang NTT.  The researcher focuses on evaluating the students’ writing ability in five aspects of writing namely content, organization, grammar, vocabulary, and mechanics.  The researcher applied the quantitative method and descriptive analysis design. The research was conducted in August 2019. This research was conducted at First semester students of the English Study Program of Nusa Cendana University, Kupang.  The population of this research was First semester students of the English Study Program of Nusa Cendana University, Kupang in the 2020/2021 academic year. The number population is 160 in four classes. The researcher took 5 students from each class as the sample of the research.  Therefore, there were 20 students as a sample. The test was used to find out the students’ ability in writing explanation text.  In collecting data, the researcher asked the students to write an argumentative essay by choosing one of the given topics. To analyze the data, the researcher focused on evaluating the students’ writing in five criteria. The result of the research shows that the mean score of the test is 6.86. It shows that the students have an average degree of capability in writing explanation text.   The biggest problem for the students in developing an explanation text is the organization (43%), it followed by the language use (37%), vocabulary (33%), content (30%), and the smallest problem is mechanics (30%).  Some factors that hamper the students in writing: 1) the students face difficulties in expressing ideas, choosing appropriate words, and arranging ideas in writing, 2) the students seldom practice their writing skill, 3) the students still find difficulty in using punctuation in writing from, 4) the students do not enrich themselves with knowledge.